Reliability and Validity of Malay Language Version of International Physical Activity Questionnaire (IPAQ-M) among the Malaysian Cohort Participants - Norsham Shamsuddin,; Poh, Bee Koon; Syed Zulkifli Syed Zakaria,; Mohd Ismail Noor,; Rahman Jamal, (Universiti Kebangsaan Malaysia, 2015)
Introduction Validation of instruments is essential when assessing physical activity (PA).The aim of this study was to validate a Malay language version of the International Physical Activity Questionnaire (IPAQ-M) against Actical accelerometer and to determine its reliability and validity. Methods A total of 90 Malay adults aged 35-65 years old participating in The Malaysian Cohort project were recruited for this study. The IPAQ-M is comprised of 12 items, covering vigorous, moderate, walking, sitting and sleeping activities, and was administered on two occasions (Day 1 and Day 9) by interviewing the participants. Participants wore the Actical accelerometer for seven consecutive days between the two interview sessions. Results Validity tests showed that time spent in moderate-vigorous physical activity (MVPA) (min wk-1) from IPAQ-M was significantly correlated with MVPA from accelerometer (=0.32, p<0.01). Time spent in vigorous activity (=0.44) and total activity (=0.36) from IPAQ-M were significantly correlated (p<0.01) with that measured by accelerometer, but no correlation was observed for sedentary behaviour. Reliability tests revealed significant correlations between the two interview sessions for all intensities of PA (=0.55 to 0.71, p<0.01). Bland-Altman plots showed that time spent in MVPA for IPAQ-M was significantly different from that measured by accelerometer (mean difference: 98.02 min wk-1; 95% limits of agreement: - 785.33 to 1317.83 min wk-1; p<0.01). When classifying people into meeting PA recommendation, the agreement between the two instruments was fair (κ=0.22). Conclusions The IPAQ-M has acceptable validity for MVPA, vigorous and total physical activity, and was reliable for assessing the physical activity of Malay adults.